Investigação numérica do efeito do atrito na interface aço-concreto para o dimensionamento à fadiga de conectores de cisalhamento em pontes mistas - Oliveira, Lucas Emmanoel Alves de (2020)
The construction of composite steel bridges has several advantages that qualify it as a viable solution. However, in Brazil, the utilization of this structural typology is still rare, a fact that may be justified by decades of inexistence of a national technical standard for this technology, published only recently. Following the trend of the main foreign reference standards, Brazilian standard for composite bridges does not consider the beneficial effect of adherence by friction in steel-concrete interface for fatigue design of headed stud shear connectors, which could promote some economical savings without compromising their safety. The literature already shows a simplified equation that, if declared valid, could be incorporated into technical standards in order to optimize this design. However, friction coefficient determination at steel- concrete interface is still one of the biggest obstacles to this incorporation. The main objective of this paper is to investigate the transfer of stresses at steel-concrete interface of composite bridge beams to better understand the effect of friction, in order to propose a procedure for determining the value of this coefficient and to suggest a way of considering it in structural calculations. For this, the authors performed computational modeling to reproduce a composite beam real bending test, available in literature, using ANSYS software, capable of simulating different contact conditions at the interface. Equations have also been proposed to determine the friction coefficient value based on the simplified equation from literature and to determine the relationship between this coefficient and shear connectors stress. The friction coefficient obtained for the modeled beam configuration was higher than the usual, what compels a different interpretation of the equation that represents the phenomenon. Nevertheless, the test was satisfactorily reproduced. The results and validated adequacy of the simplified equation suggest that shear connectors stiffness exerts a great influence on interfacial friction, overcoming even the superficial roughness aspect.